2018
DOI: 10.1051/0004-6361/201833249
|View full text |Cite
|
Sign up to set email alerts
|

The WISSH quasars project

Abstract: We present an ALMA high-resolution (0.18″ × 0.21″) observation of the 840 μm continuum and [CII] λ157.74 μm line emission in the WISE-SDSS selected hyper-luminous (WISSH) quasi-stellar object (QSO) J1015+0020, at z ∼ 4.4. Our analysis reveals an exceptional overdensity of [CII]-emitting companions with a very small (<150 km s−1) velocity shift with respect to the QSO redshift. We report the discovery of the closest companion observed so far in submillimetre observations of high-z QSOs. It is only 2.2 kpc di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 79 publications
8
29
0
Order By: Relevance
“…However, it should be noted that the gas fractions derived for the IR QSOs in our sample are largely affected by the uncertainties of dynamical mass, e.g., the relatively smaller CO size compared to the full CO flux distribution that adopted for the dynamical mass estimates would lead to an overestimation of gas fraction (see Section 3.5). Similar results have been obtained for z ∼ 6 QSOs detected in CO emission, with a median value of M gas /M dyn = 0.16 (e.g., Wang et al 2010Wang et al , 2016Feruglio et al 2018). For comparison, the gas fraction of molecular gas to total baryonic mass of M gas /(M + M gas ) is found to have a mean value of about 0.3 in z = 1 main sequence galaxies, and the fraction increases with look-back time (e.g., Tan et al 2013;Schinnerer et al 2016;Magdis et al 2017;Tacconi et al 2018).…”
Section: Discussion 41 Host Galaxy Propertiessupporting
confidence: 84%
“…However, it should be noted that the gas fractions derived for the IR QSOs in our sample are largely affected by the uncertainties of dynamical mass, e.g., the relatively smaller CO size compared to the full CO flux distribution that adopted for the dynamical mass estimates would lead to an overestimation of gas fraction (see Section 3.5). Similar results have been obtained for z ∼ 6 QSOs detected in CO emission, with a median value of M gas /M dyn = 0.16 (e.g., Wang et al 2010Wang et al , 2016Feruglio et al 2018). For comparison, the gas fraction of molecular gas to total baryonic mass of M gas /(M + M gas ) is found to have a mean value of about 0.3 in z = 1 main sequence galaxies, and the fraction increases with look-back time (e.g., Tan et al 2013;Schinnerer et al 2016;Magdis et al 2017;Tacconi et al 2018).…”
Section: Discussion 41 Host Galaxy Propertiessupporting
confidence: 84%
“…Indeed, some studies of quasar environments at z 4 report the detection of close submillimeter galaxies (SMGs) companions on scales of R 0.5 cMpc (e.g. Trakhtenbrot et al 2017;Decarli et al 2017;Bischetti et al 2018), some of which are totally extincted or at least very faint in the rest-frame UV. The acquisition of data at radio/submillimeter wavelengths in our quasar fields would allow one to explore this possibility, and would allow measurement of the clustering properties of both optical and dusty galaxy populations around quasars simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…One FIR-bright source, J1404, presents an unusual [C II] double peak that could signal a late-stage merger. Bischetti et al (2018) found three companions around their targeted z=4.4 quasar, two of which have double-peaked line emission, while in Willott et al (2017), the high spectral and spatial resolution allows them to attribute different peaks in the [C II] line to the quasar source, a 5 kpc separated companion, and a "central excess" component between the two.…”
Section: Major Mergers Among Hostsmentioning
confidence: 99%